Enhancing Engagement and Learning Outcomes through E-Learning in Higher Education - Mulvia , Rahmadhani (Eduscape : Journal of Education Insight, 2025)
This study provides a narrative review of e-learning platforms and their effectiveness in higher education, aiming to synthesize evidence on technological innovations, pedagogical models, student engagement, and learning analytics. A systematic search was conducted across Scopus, Web of Science, and Google Scholar, using keywords such as e-learning effectiveness, higher education, student engagement, learning outcomes, and e-learning platforms. Inclusion criteria focused on peer-reviewed studies addressing higher education contexts, student experiences, and measurable learning outcomes, with selected literature screened and thematically analyzed. Findings show that e-learning technologies—including artificial intelligence, virtual reality, and mobile platforms—significantly enhance personalization, interactivity, and learner motivation. Pedagogical models such as blended learning, active learning, and gamification foster collaboration, critical thinking, and improved performance. Student engagement and trust emerged as central factors, shaped by platform usability, content relevance, and faculty support. Moreover, learning analytics play a key role in identifying at-risk students and improving instructional design, although persistent concerns remain regarding data privacy and ethical issues. Systemic challenges, including weak infrastructure, insufficient institutional capacity, and limited policy support, hinder equitable implementation, particularly in developing regions. The review emphasizes the urgency of addressing these barriers through stronger policy frameworks, institutional investment, and inclusive pedagogy. Future research should employ longitudinal approaches and pay greater attention to marginalized groups. Overall, aligning technology, pedagogy, and systemic support can transform e-learning into a powerful driver of accessibility, equity, and educational quality worldwide.